ENSURING THE ECONOMIC SECURITY OF AGRICULTURAL ENTERPRISES AS AN INSTRUMENT OF STATE REGULATION OF THE ECONOMY - Mykhnovetskyi Ю. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The article deals with the issue of ensuring the economic security of agricultural enterprises as an important tool of state regulation of the economy. The article analyses the main threats to economic security and identifies the methods and measures that can be used to increase the level of economic security in the agricultural sector. The role of state policy in creating favorable conditions for the stable development of agricultural enterprises is considered. It is determined that the economic security of agricultural enterprises is a key element of the overall economic security of the state. In the context of globalization and increasing competition in international markets, ensuring the stable development of the agricultural sector is becoming one of the priorities of state policy. It is substantiated that effective state regulation can help strengthen the economic security of agricultural enterprises, which, in turn, will ensure the country's food security and the stable development of rural areas. It is determined that in the current economic environment, all business entities should adjust the mechanism for ensuring adequate security in connection with the war in our country. The military actions in our country have necessitated the development of the agricultural sector of the economy to fulfil the country's obligations to export agricultural products. Thus, the security issues of each particular agricultural enterprise are resolved by the head of this enterprise and his/her team, as state support cannot solve all the problems of forming an appropriate level of financial condition indicators. On this basis, it is necessary to identify the key areas of organization of the system of economic security of agricultural enterprises and to outline ways to improve them. The carried-out analysis of risks in the system of economic security of agrarian enterprise will allow to ensure the sustainability and stability of business in the face of uncertainty and change. The author of the study considers it necessary to identify the key areas of organizing the system of economic security of agricultural enterprises and outline ways to improve them.